Pendidikan Tinggi Perempuan Desa Plakpak Pegantenan Pamekasan dalam Bayang-Bayang Patriarki - Mubarok, A. Khuzainol; Maimun, Maimun; Anshari, Achmad (YASIN, 2025)
This study is driven by the limited research on the struggles of rural women in pursuing higher education amidst the dominance of patriarchal culture, despite the significant impact of this phenomenon on improving human resource quality and promoting gender equality at the local level. The research aims to describe and analyze the motivation, family support, and social challenges faced by women in Plakpak Village, Pegantenan District, Pamekasan Regency in accessing higher education. A qualitative approach with a case study design was employed. Ten participants were selected through purposive sampling, consisting of five women with higher education backgrounds, three parents, and two community leaders. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that women's motivation to pursue higher education is driven by spiritual and moral values, such as the desire to gain knowledge, elevate family dignity, and challenge gender stereotypes. Parental support, particularly from mothers and fathers, emerged as a key factor in overcoming the constraints of patriarchal norms. However, community responses remain mixed, with both support and resistance toward women's roles in higher education. The study concludes that higher education enhances women's social status but has not yet fully eliminated gender disparities due to the persistent strength of patriarchal values. The implications highlight the importance of synergy between education, family, and community in fostering gender equality in alignment with the principles of justice in Islam.